Modified asphalt mixtures resistance to permanent deformations - Radziszewski, Piotr (Journal of civil engineering and management, 2007)
Permanent deformations, primarily in the form of ruts, are one of the basic asphalt pavement damages impairing its service properties. Application of appropriate asphalt mixtures and binder modification are effective methods for improving asphalt courses resistance. While being manufactured, stored, fitted into a road pavement and during long term service, bitumen binders and asphalt mixtures are subject to continuous unfavourable ageing processes during which pavement courses characteristics change considerably, resistance to permanent deformations being among them. This article presents rut and dynamic creep test results of concrete, SMA (stone mastic asphalt), MNU (thin courses of non-continuous grain mixtures), Superpave mixture and porous asphalt mixture of two air void content percentages: 15 %, 20 %. Asphalt concrete mixtures, MNU's and porous asphalt mixtures contained elastomer, plastomer and fine rubber modified binders. Samples for laboratory rut tests were made by slab compaction because this method, as the author's previous research had shown, was the closest to 'in-situ' conditions. Resistance to permanent deformations of the examined specimens was evaluated before aging, after technological aging (short term ageing) and after service ageing (long-term ageing). The test results show that resistance to permanent deformations depends on the kind of asphalt mixture and binder applied. Concrete asphalts with fine rubber modified bitumens and concrete asphalts with 7 % polymer modified binders as well as SMA's and Superpave mixtures with unmodified binders appeared to be most resistant to permanent deformations after a long-term laboratory ageing. It was proved that the overall evaluation of resistance to permanent deformations could be obtained by rut and creep testing of asphalt mixtures exposed to short- and long-term ageing. Simultaneous determining 4 parameters: maximum rut depth after short-term ageing, rutting coefficient after operational ageing, stiffness creeping modulus after long-term ageing and cumulated deformation after short-term ageing, facilitates full characteristics of modified asphalt mixes designed to be built in the wearing course of a road pavement.